FACTORS AFFECTING THE MANAGEMENT OF TRAUMATIC COLONIC INJURY - Ata-ul-Lateef; Maham Mansoor Rana (Journal of University Medical & Dental College, 2019)
BACKGROUND: The main purpose behind conducting this study was to assess the eﬀect of various factors in the management of colonic injuries and their outcome; and to propose a safe and valid protocol for the management of such injuries.METHODS: 66 patients presenting with colonic injuries through emergency in General Surgical Unit of Allied Hospital Faisalabad were included in our study.RESULTS: The patients had an average age of 28 years, 73% being male. Forty-one patients underwent primary repair of the colon while 25 patients underwent fecal diversion. The time interval between injury and repair was less than 6 hours in 71% of patients. 67% of the patients sustained a gunshot wound to the abdomen, 15% were stab wounds and 18% were blunt injury. The associated abdominal organ injury was presented in most of the patients. Primary repair done in 62% patients and colostomies performed in 38% patients. The mortality rate was 14%.CONCLUSIONS: Several Factors contribute to the colon related post operative morbidity of patients and hence the treatment option such as: units of blood transfusion, multiorgan injuries, colon injury score, Injury Severity Score and degree of contamination. (p value <0.05 signiﬁcant)